PEMBELAJARAN TEMATIK PADA KELAS AWAL SEKOLAH DASAR (STUDI SITUS SD IT IZZATUL ISLAM KECAMATAN GETASAN KABUPATEN SEMARANG) - Sunarmi , Sunarmi (2011)
The objectives of this research are to describe (1) the inside classroom interaction characteristics between teachers and students in thematic learning in the beginning classroom of Islamic Elementary School IZZATUL ISLAM Getasan Semarang. (2) The outside classroom characteristics between teachers and students in thematic learning in the beginning classroom of Islamic Elementary School IZZATUL ISLAM Getasan Semarang. This is qualitative research. The research is conducted in Islamic Elementary School IZZATUL ISLAM Getasan. The main subjects in this research are principal, and teachers. Methods of data collection used interviews, observation, and documentation. The data analysis starts from (1) data reduction, (2) presentation of data, and (3) making inferences. Test the validity of data using credibility, transferability, conformabilities and dependability. The results of this research are (1) the interaction between teachers and students in beginning classes of thematic learning in Islamic Elementary School IZZATUL ISLAM Getasan is highly interactive according to the learning plan that compiled before. Thematic learning in the classroom is taught by two teachers that explain the material according to theme on learning plan, students is asking and giving an opinion when the activity is take place. Teachers organize the subject matter with the media, the use of student worksheets and also closer to students with learning resources, and also choosing material used spider web. Formation of learning groups by teachers in Islamic Elementary School IZZATUL ISLAM is giving students the opportunity to write, read, explained, and demonstrated the material in front of the classroom. (2) The outside classroom characteristics between teachers and students in thematic learning in the beginning classroom of Islamic Elementary School IZZATUL ISLAM Getasan Semarang is build used constructivism principle. The activity is done by giving an opportunity to student to build their own knowledge. The student is active in every level that is asking by teacher and doing their job such as weighing and mix the water and salt. Teacher is doing three activities so that student will be understood about the material and can implement in their life. That activity is involve (to engage), explore (to explore), and elaborate (to elaborate).